A translationally controlled tumor protein (TCTP) is involved in growth and antagonistic behaviour of Trichoderma virens. (April 2021) - Bansal, Ravindra; Gupta, Gagan Deep; Mukherjee, Prasun K.
Abstract: Translationally controlled tumour proteins (TCTPs) are omnipresent in eukaryotes and play important physiological roles. This protein is identified as an allergen in the fungi Alternaria alternata and Cladosporium herbarum, and is involved in maintaining a balance between sexual and asexual differentiation in Aspergillus nidulans . MoTCTP regulates growth and conidiation in the plant pathogen Magnaporthe oryzae . We present here the functions of a TCTP orthologue (Tcp1) in the plant beneficial fungus Trichoderma virens . T. virens Tcp1 shares 42.94% and 39.88% sequence similarity with the evolutionarily distant human TCTP and maize TCTP, respectively. Based on prediction models, the secondary structure elements (α-helices and β-sheets) were found to be very well conserved barring a few insertions/deletions in the loop region. Using homologous recombination, we obtained three independent deletion mutants in this gene and a comparison of phenotypes with the wild type strain revealed that this protein has multiple functions in T. virens . Tcp1 knockout mutants showed slow radial growth and dry weight production. Δtcp1 mutants also lost the ability to overgrow the plant pathogenic fungi Sclerotium rolfsii and Rhizoctonia solani, but retained this property against the oomycete Pythium aphanidermatum reflecting selective loss of antagonistic ability. The mutants also lost the ability to colonize and kill the sclerotia of S. rolfsii . Highlights: T. virens mutants in a translationally controlled tumor protein (TCTP) obtained through gene deletion approach. T. virens TCTP mutants had reduced growth rate and conidiation. The mutants lost the ability to colonize two soil-borne plant pathogenic fungi. TCTP mutants lost their ability to parasitize the sclerotia of S. rolfsii.